PENGARUH PENGGUNAAN TIPE PENGEMAS YANG BERBEDA TERHADAP KARAKTERISTIK KERIPIK JAMUR TIRAM: The Effect of Using Different Types of Packaging on the Characteristics of Oyster Mushroom Chips - Hardiyanto, Rosiana Ulfa, Bagus Setyawan (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2022)
favored by the community is processed food from mushrooms, especially oyster mushrooms. Oyster mushroom is one type of plant that is rich in nutritional content and its cultivation is easy and economical. Besides being rich in vitamins and fiber, mushrooms also contain minerals such as potassium, calcium, sodium, phosphorus, iron, and magnesium. The purpose of this study is to give the effect of the type of packaging on the chemical characteristics of oyster mushroom chips. And there is an effect of the type of packaging on consumer preferences. This study used a completely randomized design (CRD) method with 5 treatments and 4 replications. As a treatment, the types of packaging include Polypropylene (PP), Polyethylene (PE), Low-Density Polyethylene (LDPE), Aluminum foil, and Aluminum + plastic. The test parameters used were Moisture Content, Free Fatty Acid (FFA), and Organoleptic. The results showed that the test with Aluminum foil + plastic packaging gave the best value of 0.65%. The best test on Polyethylene packaging with a value of 0.028%. For the best results in the organoleptic test, the aroma of the Aluminum foil packaging was 3.27%, the color in the Aluminum foil + plastic package was 3.4%, and the texture in the Polypropylene package was 3.32%.